Graphene-based microfluidics for serial crystallography. Issue 16 (31st May 2016) - Sui, Shuo; Wang, Yuxi; Kolewe, Kristopher W.; Srajer, Vukica; Henning, Robert; Schiffman, Jessica D.; Dimitrakopoulos, Christos; Perry, Sarah L.
Abstract : A robust strategy for the incorporation of graphene films as a diffusion barrier in ultra-thin X-ray compatible microfluidic devices. Abstract : Microfluidic strategies to enable the growth and subsequent serial crystallographic analysis of micro-crystals have the potential to facilitate both structural characterization and dynamic structural studies of protein targets that have been resistant to single-crystal strategies. However, adapting microfluidic crystallization platforms for micro-crystallography requires a dramatic decrease in the overall device thickness. We report a robust strategy for the straightforward incorporation of single-layer graphene into ultra-thin microfluidic devices. This architecture allows for a total material thickness of only ∼1 μm, facilitating on-chip X-ray diffraction analysis while creating a sample environment that is stable against significant water loss over several weeks. We demonstrate excellent signal-to-noise in our X-ray diffraction measurements using a 1.5 μs polychromatic X-ray exposure, and validate our approach via on-chip structure determination using hen egg white lysozyme (HEWL) as a model system. Although this work is focused on the use of graphene for protein crystallography, we anticipate that this technology should find utility in a wide range of both X-ray and other lab on a chip applications.